An influence of vapours of some organic compounds and water on acoustic properties of selected polymer layers - JAKUBIK, W.; URBAŃCZYK, M. (Archives of Acoustics, 1993)
The present paper deals with an investigation of the interaction of thin polymer layers with on ambient atmosphere in view to using them to design gas sensors. The changes in physical properties of a polymer layer were recorded as a change in a differential frequency of dual acoustic delay line with a surface wave. The preliminary results demonstrate a selective sensitivity of polymer layers to gases in the ambient atmosphere.